Serum HIF-1α and TGF-β1 levels depending on the clinical and morphological characteristics of breast cancer and sensitivity of tumor to neoadjuvant chemotherapy - E. Yu. Zubareva; M. A. Senchukova; E. V. Virich; M. R. Zubarev; M. A. Goncharova (Исследования и практика в медицине, 2021)
Purpose of the study. To assess the serum levels of HIF-1 α and TGF-β1 in patients with invasive breast cancer (BC) depending on the clinical and morphological characteristics, molecular biological subtypes and the degree of pathological response (PR) of the tumor and metastases in the regional lymph nodes.Materials and methods. 65 patients with newly diagnosed invasive BC, of whom 32 received from 6 to 8 courses of neoadjuvant chemotherapy (neo-A-CT) were included in this pilot study. The levels of TGF-β1 and HIF-1α were determined by enzyme-linked immunosorbent assay. Statistical analysis was performed using the Statistica 12.0 software.Results. It was found that a high level of TGF-β1 was significantly more often observed in HER2-positive and I-IIa stages of luminal A and triple-negative BC (p = 0.01). HIF-1a levels were significantly higher in the presence of distant metastases (p = 0.04) and slightly higher in the presence of microcalcifications on mammograms (p = 0.07).The analysis showed that patients with grade III-IV of PR in tumor were significantly younger (p = 0.047). Grade III-IV of PR in tumor was significantly more often observed in G3 (p = 0.05), in Her2-positive and triple negative BC (p = 0.01), in the absence of perineural (p = 0.002) and lymphovascular invasion (LVI) (p = 0.045), in the presence of lymphoid infiltration (p = 0.011) and microcalcifications in the tumor (p = 0.043), and slightly higher in ductal BC (p = 0.08). No significant correlations were found between the levels of TGF-β1 and HIF-1a and tumor PR (p = 0.6 and p = 0.9, respectively). However, in patients with grade III-IV of PR in regional metastases, the level of TGF-β1 was significantly lower than in patients with grade I-II (p = 0.03).Conclusions. Thus, these data indicate the presence of correlations between the levels of HIF-1 α and TGF-β1 in the blood serum and a number of clinical characteristics of BC. The highest levels of HIF-1α are observed in the presence of distant metastases, and the highest levels of TGF-β1 are noted in HER2-positive and I-IIa stages of luminal A and triple-negative breast cancer. Given the presence of significant correlations between the level of TGF-β1 and the degree of PR in regional lymph nodes, its determination may be useful for assessing the sensitivity of metastases to regional lymph nodes to the neo-A-CT.